Effect of different coupling agent on properties of coconut shell powder reinforced natural rubber composites / \c Haryanti binti Ibrahim. - Haryanti Ibrahim (School of Material Engineering, Universiti Malaysia Perlis, 2010)
The objective of this study is to investigate the feasibility of coconut shell powder as fillers in natural rubber (NR) composites with an aim of developing rubber composites.